PEMBUATAN BIOETANOL DARI NIRA NIPAH SECARA SEMI SINAMBUNG (FEDBATCH) DENGAN PENAMBAHAN UREA DAN CORDYCEPS MYCELLIUM - Dede putra pranata; Fajar Restuhadi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of  this study was to obtain best combination urea and Cordyceps mycellium on the quality of concentration ethanol. The research was implemented to determine the optimization  production of bioethanol by fermentation method technique Very high gravity fermentation (VHGF) with free cell to see the effect of the combination treatment in an increase in bioethanol. This research was conducted an experiment with two factors, the first factor is Urea which consists of four levels and the second factor isCordyceps mycellium consisting of three levels each treatment combination obtained twelve experimental units. Combination of Urea levels are U1 (0 g/l); U2 (0.2 g/l); U3 (0.4 g/l); U4 (0.6 g/l), while the combination of Cordyceps mycelliumlevels C1 (0 g/l); C2 (0.5 g/l); C3 (1 g/l). Observations were made every 24 hours; covering sugar, ethanol content, the number of cells, and pH. The data were analyzed descriptively by using a tabular or graphical. The best treatment isa combination of U2C2 (Urea 0.2 g/l and Cordyceps mycelium0.5 g/l) that resulted in the largest ethanol 22.5%. Keywords: Nypa sap, VHGF, Bioethanol, Cordyceps mycellium, and Urea